Intellectual disability, unusual facial morphology and hand anomalies in sibs - Sousa, SB (2013)
Here we report on a Portuguese family with three sisters who shared moderate intellectual disability, unusual facial morphology (short palpebral fissures; broad nasal tip; thin upper and lower vermillion; broad and pointed chin) and hand anomalies in two of them (short left third and fifth right metacarpals in one case; marked syndactyly between the third and fourth fingers in another). One of the sisters had microcephaly and short stature, and the other two were obese. Obesity and somewhat similar facial features were also present in the otherwise healthy mother. Despite the overlap with several known syndromes (Albright osteodystrophy; Filippi syndrome; Rubinstein-Taybi syndrome; microdeletion 2q37), we suggest this condition is previously unreported, and most likely displays an autosomal recessive pattern of inheritance.